المقاصد الشرعية في التشريع الإسلامي على ضوء القرآن والسنة - Mohamed Fathy, Mohamed Abdelgelil; Mohd Safri, Ali; Najihah, Abd Wahid; Zawawi, Yusoff (2018)
Who can distinguish the “Objectives of Shari‘ah (Maqasid al-Shari‘ah)” is eligible to exercise the juristic interpretation (Ijtihad). His juristic interpretation supplements to comprehension the maxims of the Law-giver. The optimal method to utilize the sayings, connotations, ordinances, objectives, rationale, and outline of what are seemingly unpredictable and outweighing of the nearest proofs to the Maqasid al-Shari‘ah. Therefore it is obvious that Maqasid al-Shari‘ah is crucial to be dealt with, especially after the proliferation of Shari‘ah critics and abounding of contemporary and apprising issues. Hence Islam demonstrates to be a civilized religion that is valid for all times and places. However, calling for stimulation of “Objectives of Shari‘ah (Maqasid al-Shari‘ah)” in life is not a cause for alienation of Legal Texts and this is the research problem statement. Therefore, this research aims to appeal the educational institutions to introduce the substance of “Objectives of Shari‘ah (Maqasid al-Shari‘ah)” within their curricula. The educational institutions enable to ensure an intellectual enlightenment and a balanced (wasatiyah) mindset that effectively revive the divinity of religion to exalted its highest ranks providing an explanation that these objectives of Shari‘ah are validly comprehensible. This study employed the analytical method that resulted in Maqasid al-Shari‘ah could be found in the fatwas and statements of the early righteous ulema (Ulema al Salaf) but without any specialization. Consequently, this type of knowledge (juristic interpretation /Ijtihad) must derive from the texts of the Holy Qur’an and from the Prophetic Tradition (Sunnah) combined the adoption of specific texts to extract the “Objectives of Shari‘ah (Maqasid al-Shari‘ah)”.